Female sexuality : new psychoanalytic views - Chasseguet-Smirgel, Janine, 1928-2006 (Maresfield library., 1992)
Contains six essays and an introduction on Freudian and non-Freudian views of female sexuality. Contributors include Joyce McDougall, Maria Torok and Bela Grunberger.